2004
DOI: 10.1139/x03-214
|View full text |Cite
|
Sign up to set email alerts
|

Tree rings from a European beech forest chronosequence are useful for detecting growth trends and carbon sequestration

Abstract: Past carbon (C) storage trends were estimated using dendroecological methods in a beech chronosequence in central Germany. Raw-ring-width chronologies, sensitivity curves, and carbon uptake trends were developed for 70-, 110-, and 150-year-old (S70, S110, and S150), even-aged stands. Ecosystem C stock and net ecosystem productivity (NEP C ) were computed as the sum of the C stock and fluxes of the soil, the aboveground compartment, and the estimated belowground compartment. The ecosystem C stock ranged from 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…A one-stage Randomised Branching Sampling (RBS) was used to upscale stem C increments to the stand-level [3,17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A one-stage Randomised Branching Sampling (RBS) was used to upscale stem C increments to the stand-level [3,17].…”
Section: Methodsmentioning
confidence: 99%
“…A number of direct (on a destructive sampling basis) and non-direct (on increments monitoring grounds) have been put into practise in the past. Destructive biomass samplings can be coupled to stem net primary production measures in order to assess yearly C increment pattern [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…Different methods of dendrochronological analysis were often used to evaluate the impact of pollution on the potential incremental trees (McLaughlin et al, 2002;Bascietto et al, 2004;Battipaglia et al, 2009;Eckstein and Schweingruber, 2009), A number of studies have investigated: the rate of trees with different degrees of growth reduction to the diameter and height (Kienast, 1985;Schweingruber, 1986;Danek, 2007;Elling et al, 2009;Malik et al, 2012;Crecente-Campo et al, 2010), differences in similarity in radial growth response of trees (Wilczynski, 2006). Scientific literature reviews have shown that, the size of reduction also depends on the distance from the source of pollution, directions prevailing winds and area orography (Krąpiec and Szychowska Krąpiec, 2001;Juknys et al, 2003Juknys et al, , 2014Wilczyński, 2006;Elling et al, 2009;Malik et al, 2012;Rydval and Wilson, 2012;Bošela et al, 2014).…”
Section: Trees As Bio-indicatorsmentioning
confidence: 99%
“…The comparable fall in BAI reported by Piovesan et al (2005b) suggests that this climate-related decline in the growth of F. sylvatica at the edge of its range in Montseny is not an isolated phenomenon, but may be occurring at the southern range edge of this species elsewhere in Europe. F. sylvatica is an increasingly important species for European forestry (Dittmar et al, 2003) and therefore a highly significant species in terms of carbon sequestration (Bascietto et al, 2004). Recent climatic warming has increased the length of the growing season for many species in the Montseny region (Peñ uelas et al, 2002), suggesting a positive growth response to recent climatic changes might be expected for F. sylvatica.…”
Section: Bai Related To Altitudementioning
confidence: 99%